Buddhist Monks And Community Development Along the Lines of Sufficiency Economy - Wananpirun, Trinik (Journal of Dhamma for Life, 2026)
This study aims to analyze the role of Buddhist monks as a key mechanism in strengthening community resilience, particularly in promoting the Sufficiency Economy Philosophy at the local level. The findings reveal that monks play an active role as both spiritual and social leaders who maintain close relationships with communities across multiple dimensions, including religious rituals, education, moral and ethical development, counseling, and mediation of family and community conflicts. Moreover, monks serve as important intermediaries between the state and local communities by facilitating the dissemination of public knowledge and policies, particularly in communicating the principles of the Sufficiency Economy Philosophy and the New Theory to support practical application in everyday life. The study generates new insights indicating that Buddhist monks’ function not only as religious leaders but also as holders of cultural social capital that contributes significantly to community strengthening. This is achieved through the integration of Buddhist teachings with sustainable development concepts, particularly the application of the Sufficiency Economy Philosophy to improve people’s quality of life in a tangible manner. The findings highlight the importance of enhancing the role of monks within participatory community development systems to foster long-term sustainability in social, economic, and cultural dimensions.